OPTIMASI KAPASITAS PRODUKSI PADA USAHA KECIL MENENGAH SARI RASA LESTARI - Putri Edlin Solva; Elsya Paskaria Loyda Tarigan (LPPM Universitas Putera Batam, 2024)
The production process is an activity that can produce quality products. The production process can determine whether the product is good or bad. when the process runs optimally, the results will be optimal and vice versa. Sari Rasa Lestari Small and Medium Business is an SME located in Taman Lestari, Batu Aji, Batam., and is a business that is engaged in producing noodles. The aim of the research is to find out the combination of products that can produce maximum profits. The method used in this research is Linear Programming, the simplex method. The results of the mathematical calculations in the first iteration are the value X1 = 1250kg with the value Zmax = IDR 2,125,000.00. , Because the Z value is still negative, iterations are carried out until the Z value is not negative, namely in the fourth iteration with the resulting values ​​X1=1250kg, X2=1415.7kg, X3=761.7kg and X4=600 kg with a profit of Rp. 6,458,667 every month. Thus, the Sari Rasa Lestari Small and Medium Enterprises only produce x1, x2, x3 and x4 every month to get maximum profits